EFFECT OF SERVANT LEADERSHIP BEHAVIOR ON WORK DESIGN: KNOWLEDGE CHARACTERISTICS ANALYSIS - Indartono, Setyabudi (Journal of Management and Business, 2010)
This study investigates the complexities effect of servant leadership and Work Design of Morgeson’s. This study proposed hypotheses on each dimension of servant leadership behavior and each dimension of knowledge characteristics of work design. This Study collected data from 537 employees from various businesses in Indonesia and Taiwan. The Structural Equation modeling was used to investigate the model of fit. The multiple regressions were also used to test the effect of each servant leadership dimension to the dimensions of knowledge characteristics. This study found that empowerment of servant leadership behavior has an effect to all dimensions of knowledge characteristics, significantly. The service behavior of leader has also significant effect on skill variety of work design. Implication of the findings for organizations and suggestions for future research are discussed.